Association between domestic animal exposure and diarrhea prevalence in under- five children in low- and middle-income countries: a systematic review and meta-analysis - Atalay Getachew; Mesafint Molla; Amha Admasie; Muluken Azage Yenesew (BMC, 2024)
Abstract Background Diarrheal disease is still the leading cause of morbidity and mortality in children, despite significant progress in diarrhea interventions. Zoonotic transmission is the main cause of the emergence and re-emergence of diseases. Domestic animals are often close to humans, particularly in resource-poor countries. Despite evidence of environmental contamination, there have been limited studies conducted to examine the association between domestic animal exposure and diarrheal disease in low- and middle-income countries (LMIC). Therefore, this systematic review and meta-analysis examines the association between domestic animal exposure and diarrheal disease in children under five years of age in LMIC. Methods The search strategy followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines for the reporting of systematic reviews. All appropriate databases were searched to find relevant articles. Research studies were selected for review if they reported an outcome variable that measured diarrhea and exposure variables of any domestic animals. A data extraction form was used to extract information from each study. The quality of the individual articles was assessed using the Joanna Briggs Institute (JBI's) critical appraisal tools. Publication bias was checked using a funnel plot, Egger's regression test, and Begg's test. The heterogeneity of studies was checked using the Galbraith plot and the I-squared test. A sensitivity analysis was conducted, and a meta-analysis was conducted using STATA 17. Results After reviewing 113 articles, 11 articles fulfilled the inclusion criteria hence considered for meta-analysis. The finding of these 11 studies revealed that study participants who had animal exposure had 1.95 higher odds of diarrhea as compared to participants who hadn't animal exposure (OR: 1.95, 95%CI: 1.25, 2.66). Conclusions and recommendations This study reported that diarrheal disease was associated with study subjects who had domestic animal exposure. Therefore, more comprehensive research is needed on specific behaviors and interventions surrounding animal husbandry that may affect the transmission of pathogens between animals and humans; this would facilitate the design and implementation of measures to reduce animal exposure in the domestic environment.